Analisis Perencanaan Tebal Lapis Tambah (overlay) Cara Lenduntan Balik Dengan Metode Pd T-05-2005-B dan Pedoman Interim No.002/P/BM/2011 - Wahyudi, Danu; Pratomo, Priyo; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Roads are the transport infrastructures which play an important role in supporting the economicgrowth of a region. Therefore it is necessary to do maintenance efforts so that the roads canfunction optimally.One of them is by adding overlay. The selection of methods become a factorthat must be considered before doing flexible pavement overlay design. It is because of improperplanning can cause damaged or uneconomical construction of roads. Along with the technologicaladvances, methods of overlay flexible pavement design based on deflection also undergone manymodifications such as“Pedoman Perencanaan Tebal Lapis Tambah Perkerasan Lentur Pd T-05-2005-B”and “Pedoman Interim Perkerasan Jalan Lentur No.002/P/BM/201”. The purpose of thisresearch was to determine the most optimal and most efficient life cyclecost of overlay design inthe roads performance improvement project of Batas Kota Metro-Gedung Dalam. From theanalysis results show that the design results by using Pd T 05-2005-B were thinner than PedomanInterim No.002/P/BM/2011. It was caused by several factors such as the analysis of traffic,temperature correction factor, and the types of materials used. The indicator value of theinternational roughness index (IRI) is predicated by emperical equations and the design life of 20years, obtained the lowest lifecycle costs are the result of design methods Pd T-05-2005-B. Theresults of the analysis also showed that the cost at the end of the design life methods Pd T-05-2005-B less than Pedoman Interim No.002 /P/BM / 2011.Keywords :Road, Overlay, Life Cycle Cost